2010
DOI: 10.1017/s0007114509993382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cocoa flavanol consumption on blood pressure responsiveness to exercise

Abstract: Impaired endothelial vasodilatation may contribute to the exaggerated blood pressure (BP) responses to exercise in individuals who are overweight/obese. The present study investigated whether consumption of cocoa flavanols, which improve endothelium-dependent flow-mediated dilatation (FMD), can modify BP responsiveness to exercise. Twenty-one volunteers (eight females and thirteen males, 54·9 (SE 2·2) years, BMI 31·6 (SE 0·8) kg/m 2 , systolic BP 134 (SE 2) mmHg, diastolic BP (DBP) 87 (SE 2) mmHg) were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Other species were confirmed as having laxative, hepatoprotective and hypolipidemic properties. The species that was submitted to the highest number of studies was T. cacao L., which seeds showed anticancer (Jourdain, Tenca, Deguercy, Troplin, & Poelman, 2006;Ohno, Sakamoto, Ishizuka, & Fujita, 2009), antidiabetic (Ruzaidi, Amin, Nawalyah, Hamid, & Faizul, 2005), anti-inflammatory (Kim et al, 2010), antioxidant (Crozier et al, 2011;Sakagami et al, 2008;Sarmadi, Ismail, & Hamid, 2011;Spadafranca, Martinez, Sirini, & Testolin, 2010), cardioprotective (Allen, Carson, Kwik-Uribe, Evans, & Erdman, 2008;Balzer et al, 2008;Berry, Davison, Coates, Buckley, & Howe, 2010;Buijsse, Feskens, Kok, & Kromhout, 2006;Fisher, Hughes, Gerhard-Herman, & Hollenberg, 2003;Grassi et al, 2008;Heiss, Dejam, & Kleinbongard, 2003;Jia et al, 2010;Rein, Paglieroni, & Wun, 2000;Wang-Polagruto et al, 2006) (data not show in Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Other species were confirmed as having laxative, hepatoprotective and hypolipidemic properties. The species that was submitted to the highest number of studies was T. cacao L., which seeds showed anticancer (Jourdain, Tenca, Deguercy, Troplin, & Poelman, 2006;Ohno, Sakamoto, Ishizuka, & Fujita, 2009), antidiabetic (Ruzaidi, Amin, Nawalyah, Hamid, & Faizul, 2005), anti-inflammatory (Kim et al, 2010), antioxidant (Crozier et al, 2011;Sakagami et al, 2008;Sarmadi, Ismail, & Hamid, 2011;Spadafranca, Martinez, Sirini, & Testolin, 2010), cardioprotective (Allen, Carson, Kwik-Uribe, Evans, & Erdman, 2008;Balzer et al, 2008;Berry, Davison, Coates, Buckley, & Howe, 2010;Buijsse, Feskens, Kok, & Kromhout, 2006;Fisher, Hughes, Gerhard-Herman, & Hollenberg, 2003;Grassi et al, 2008;Heiss, Dejam, & Kleinbongard, 2003;Jia et al, 2010;Rein, Paglieroni, & Wun, 2000;Wang-Polagruto et al, 2006) (data not show in Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Crews et al did not observe any change in BP among healthy men and women over the age of 60 who consumed both a cocoa beverage and dark chocolate daily for 6 weeks (providing a total of 754.71 mg proanthocyanins), relative to those consuming low-flavanol control products (45). However, Berry and colleagues demonstrated that consumption of a high-flavanol (701 mg) cocoa beverage could significantly improve BP response to exercise compared to a low-flavanol (22 mg) beverage (21).…”
Section: E Effects On Bpmentioning
confidence: 99%
“…A number of observational studies have demonstrated a negative relationship between habitual cocoa intake and blood pressure (53 -55) . This is supported by cocoa intervention studies showing a reduction in blood pressure in healthy participants (56,57) , as well as in participants who are overweight (58,59) and in those with evidence of glucose intolerance or cardiovascular risk factors (60 -63) .…”
Section: Concomitant Active Components and Their Mechanismsmentioning
confidence: 84%